Functional Pattern of Benthic Epifauna in the Chukchi Borderland, Arctic Deep Sea - Zhulay, Irina; Bluhm, Bodil A.; Renaud, Paul E.; Degen, Renate; Iken, Katrin (Frontiers in Marine Science, 2021)
Assessment of Arctic deep-sea ecosystem functioning is currently an urgent task considering that ongoing sea-ice reduction opens opportunities for resource exploitation of yet understudied deep-sea regions. We used Biological Trait Analysis to evaluate ecosystem functioning and test if common paradigms for deep-sea fauna apply to benthic epifauna of the deep-sea Arctic Chukchi Borderland. We also investigated the influence of environmental factors on the functional structure of the epifauna. The analysis was performed for 106 taxa collected with a beam trawl and a Remotely Operated Vehicle from 486 – 2610 m depth. The most common trait modalities were small-medium size, mobile, benthic direct and lecithotrophic larval development, and predatory feeding, which mostly supports the current view of epifauna in the global deep sea. Functional composition of epifauna differed between two depth strata (486 – 1059 m and 1882 – 2610 m), with depth and sediment carbon content explaining most of the functional variability. Proportional abundances of the modalities free-living, swimming, suspension feeders, opportunists/scavengers, internal fertilization and globulose were higher at deep stations. Functional redundancy was also higher there compared to the mid-depth stations, suggesting adaptation of fauna to the more homogeneous deep environment by fewer and shared traits. Mid-depth stations represented higher functional variability in terms of both trait modality composition and functional diversity, indicating more variable resource use in the more heterogeneous habitat. Food input correlated positively with the proportional abundance of the modalities tube-dwelling, sessile and deposit feeding. Areas with drop stones were associated with higher proportional abundance of the modalities attached, upright, and predators. Comparatively low functional redundancy may render the heterogeneous mid-depth area of the Chukchi Borderland vulnerable to disturbance through the risk of loss of functions. Across the study area, high occurrence of taxa with low dispersal ability among adult and larval life stages may prevent rapid adaptation to changes, reduce ability to recolonize and escape perturbation.